Moroccan Folktales Translated into English: A Bibliographical Article الحكايات الشعبية المغربية المترجمة إلى اللغة الإنجليزية: مقال بيبليوغرافي - Mouna Hajjaj; Jamaa Ouchouid (Indonesian Scientific Publication, 2026)
Translators and researchers tend to document and translate different oral genres, namely, folktales. The present bibliographical article describes eighteen works that are devoted to translating Moroccan folktales into English by Moroccan and non-Moroccan translators. Following the chronological order of these translations, the article aims to provide researchers with an overview of these works by focusing on folktale types, the collection process, and the translation approaches adopted in each work. The article demonstrates that both Moroccan and non-Moroccan translators aim to record Moroccan orality in English and provide valuable material for academic researchers to investigate the translation of orality.